Designing a virtual breast cancer prevention program for Iranian women: A study protocol - Nayereh Naseri; Fariba Taleghani; Maryam Sadat Hashemi; Arash Najimi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The growing number of breast cancer patients in Iran, following the lower referrals of women to screening centers after the outbreak of the COVID-19, suggests the need for designing virtual educational interventions to teach self-care methods to women. The aim of this study is to design a virtual training program for the prevention of breast cancer in women based on the steps of the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) educational design model. MATERIALS AND METHODS: This developmental study will be conducted based on the steps of the ADDIE model. In the first step (analysis), a qualitative study, literature review, and a panel of experts will be conducted to analyze the situation (learners, content, platforms, and media for the electronic presentation of the program). In the design step, the learning objectives, educational strategies, and the way of program's implementation and evaluation will be specified. In the third step, not only are the content, storyboard, and educational program developed, but the pilot study is also conducted and formative assessment is performed. In the fourth step, the program will be provided to the audience and will be implemented as a preliminary program. In the final step, the final virtual education program for the prevention of breast cancer in women will be presented based on the results of the evaluation. CONCLUSIONS: Using a comprehensive and systematic educational design model can be a step toward making changes and encouraging innovations in breast cancer prevention education programs in women based on virtual education. Given the existing needs and conditions, this program can promote cancer preventive behaviors as much as possible, reduce the costs imposed on the family and healthcare systems, and lower the complications and mortality rate caused by the delayed diagnosis of the disease.